Leadership and personality influence on creativity - Ghazali, Sabarani; Johari, Husna; Othman, Abdul Aziz (2014)
Creativity is a pertinent agenda in ensuring the success of an organisation in the face of stiff global competition.Creativity is a trait that can be instilled within an individual, other than occurring naturally. In a person, creativity can result from the interaction between two factors, namely situational factor(external factors to the individual) and person factor (internal factors of the individual).This research focuses on the influence of work design on creativity among workers.Additionally, this study also looked at the influence of leadership moderator (one of the situational factors) and personality (a person factor), toward the relationship between work design and creativity among workers.A total of 158 respondents answered the questionnaire given in this cross-sectional study. Results from the correlational and regression analyses showed that work design has a significant relationship with creativity. Also, results from the hierarchical regression analysis revealed that the personality factor has a stronger moderating effect as compared to the leadership factor toward the relationship between work design and creativity.This shows that the person factor gives a greater effect as compared to the situational factors for forming creativity. Based on the results of this research, several management actions are recommended for enhancing creativity amongst employees at the workplace.In addition, theoretical implications were also discussed in view of the research limitations which were observed.At the end of this paper, future research directions are also presented.